Que cachent les « termes barbares » de la crise financière internationale ? - Pascale Janot (Corela)
With the international financial crisis (2008), a series of primarily Anglo-Saxon terms began to be propelled to the forefront of the media. Journalists/commentors were thus forced to try to gloss and 'popularise' a highly specialised jargon that was incomprehensible for most of their audiences. Along the discursive chain of these 'words from elsewhere', which constituted the interface between the enunciator (journalist-divulgator) and the language of 'the Other' (the specialised economic terminology), a metalinguistic, evaluative commentary began to insinuate itself, e.g.: 'Hidden behind this barbaric term...', 'known by the barbaric term of...', 'this barbaric sigla designates...', etc. The present article examines the use of 'barbaric' as conferring a specific alterity to the terminology in question. It will do so by examining how terms defined or characterised in this way are specifically reformulated, and by analysing the discursive function of this characterisation.